Stunting Case Study In Grogol Bejiharjo Karangmojo Gunungkidul D. I. Yogyakarta, Indonesia Based On Routine Blood Examination - Fadhilah, Siti; Astuti, Dian Wuri; Dewi, Eltanina Ulfameytalia; Muhajir, Nurlaili Farida (Jurnal EduHealth, 2022)
Background: Stunting is defined as the condition of the nutritional status of toddlers who have a height that is classified as less when compared to age. The prevalence rate of stunting under five nationally in 2021 is 24.4%. Objective: The research aims to describe stunting cases in Grogol Bejiharjo Karangmojo Gunung Kidul D.I.Yogyakarta Indonesia based on routine blood tests. Methods: The design of this study used observational analysis with the independent-T test. The number of respondents involved as many as 14 respondents with the purposive sampling method. Results: The number of respondents categorized as stunting based on measurements of height per age (TB/U) was 64.3% consisting of concise and short nutritional status. This number is higher than those who are not stunted (normal), which is 35.7%. The number of leukocytes in the low-stunted group tends to be lower than in the normal (non-stunted) group, as well as the parameters of the lymphocyte count examination that the average result is higher in the stunting group compared to the normal (non-stunted) group. There was a significant difference in the average hemoglobin level between the stunting and non-stunted groups because of the p-value <0.05. A significant difference was also found in the mean hematocrit value between the stunted and non-stunted groups because of the p-value <0.05. Conclusion: statistical differences in hemoglobin levels and hematocrit values between groups. Other blood test parameters were not statistically different.